Suppression of endogenous corticosterone levels in vivo increases the steroidogenic capacity of purified rat Leydig cells in vitro. - H.-B. Gao; L X Shan; Carl Monder; M P Hardy (1996)
In vitro studies have shown that corticosterone (B) directly inhibits testosterone (T) production by purified Leydig cells but does so only at high concentrations. 11 beta-Hydroxysteroid dehydrogenase (11 beta-HSD) in Leydig cells oxidatively inactivates B, lowering its effective concentration, thus protecting against the suppressive effect of glucocorticoid on T production. The aim of the present study was to assess the significance of B at physiological levels in modulating T production and 11 beta-HSd activity in Leydig cells. To determine the effects of endogenous B on Leydig cell steroidogenesis, male rats (200-250 g body wt) were adrenalectomized (ADX), while control rats were subjected to sham surgery (SHAM). Seven days after surgery: T and LH were measured in serum; T production was measured in aliquots of spent culture media from 3-h incubations of purified Leydig cells; 11 beta-HSD activity and messenger RNA was measured in purified Leydig cells. ADX rats had elevated serum T (P < 0.05) in contrast to SHAM control or ADX rats that received B replacement (1 mg/100 g body wt per day, i.p., on the final 3 days). Serum LH levels were uninfluenced by ADX, with or without B replacement (SHAM), 0.45 +/- 0.16 ng/ml; ADX, 0.35 +/- 0.13 ng/ml; ADX + B, 0.61 +/- 0.09 ng/ml, NS, P > 0.05). This indicated that the alteration of T production was induced by a mechanism that is independent of LH. ADX nearly doubled LH-stimulated T production by purified Leydig cells, from 106.3 +/- 9.3 (SHAM) to 183.2 +/- 16.7 (ADX) ng/10(6) cells.3 h (mean +/- SEM for three replications of the experiment, P < or = 0.02). T production by Leydig cells from the ADX + B treatment group was suppressed to 53% of SHAM values, indicating that B inhibits T production after ADX. The oxidative activity of 11 beta-HSD in Leydig cells exceeded its reductive activity, and both activities declined after ADX. The decline in 11 beta-HSD activities after ADX was prevented by B replacement. Similarly, the steady state levels of 11 beta-HSD messenger RNA declined in Leydig cells after ADX, and this decline was prevented by B replacement. We conclude that physiological levels of B exert a tonic, negative control directly on Leydig cell steroidogenesis and also induce intracellular 11 beta-HSD activity, thereby protecting against B-mediated inhibition of T production. By modulating the level of active glucocorticoid in Leydig cells, 11 beta-HSD is thus a significant determinant of their steroidogenic capacity.